Virtual International Group Study Program: Towards Understanding Sustainable Development Goals and Community Development in Nepal - Walsh, Christine A.; Curties, Hana; Dhungel, Rita (Molung Educational Frontier, 2023)
To fill the gaps in international education left by the COVID-19 pandemic, many study abroad educators have become creative with their international programming by going online. This theoretical paper describes the conceptualization and delivery of a virtual collaborative program that was developed through a partnership between the Faculty of Social Work professors at the University of Calgary in Canada and Southwestern State College in Nepal. In this article, we share the model of the program and our motivations for developing the program; a formal evaluation of the model has not yet been conducted. Our pedagogical approach was grounded in anti-oppressive practices, which prioritizes the importance of engaging in empowering practices that share power based on mutual respect and learning. In our attempt to address and mitigate divides of students in the Global South and North, we sought to maximize engagement between students, educators from both institutions and social work practitioners (formal and informal) from Nepal to help promote intercultural learning. We also chose the United Nation’s Sustainable Development Goals as a site of inquiry with the aim of bridging divides and uncovering commonalities across the two countries – Canada and Nepal. With a mission to deliver an interdisciplinary approach to social work, in this paper, we outline the ways that virtual programming can be made collaborative, immersive, and experiential for all participants regardless of their global location. Lastly, the future of this program will be discussed as travel-based education reopens around the world. In presenting our model, we hope to inform the development of future anti-oppressive international education in social work.